ANALYSIS OF SCIENTIFIC RESEARCH ON ISLAMIC LAW IN EUROPE (XVIII-XXI) (Scientific journal of the Fergana State University, 2023)
The study of Eastern cultures by European Orientalists took an increasingly philological direction, avoiding generalizations in favor of detail and factuality. Despite the different reasons for the emergence of Oriental studies, this science served to the mutual enrichment of civilizations. Along with other branches of Oriental studies, Islamic studies has also being developed, the beginning of the formation of which dates back to the middle of the 19th century. Among the Islamic sciences, special attention is paid to the study of Islamic law.This article discusses the origin and development of research on Islamic law in Europe. It also analyzes the approaches of orientalists to the study of Islamic law in Europe.